Autistic Adults' Reflections on What Supported Their Transitioning from Secondary School - Louise Maree White; Kate Simpson; Stephanie Malone; Dawn Adams (MDPI AG, 2024)
Identifying ways to improve transition support for autistic students exiting secondary school is an important research priority. However, few studies have consulted with autistic/autism community members to identify how to make this support effective. This co-produced study asked autistic adults to reflect on their own transition, with the aim of identifying what was helpful and effective in supporting their transitioning from secondary school. It also aimed to identify whether there were any differences for students from non-metropolitan areas. Ten autistic adults participated in semi-structured interviews conducted online or via telephone. Interview data were analysed using thematic analysis, which generated two themes: (1) accessing opportunities that supported decision making and (2) being able to develop the "skills of adulthood". The findings suggest the importance of supporting all autistic students to explore multiple pathways to make well-informed post-school decisions. A holistic approach is needed to support autistic students in developing the logistical skills and independence needed to succeed in post-school life. This approach should include guidance from autistic role models. For autistic young people attending non-metropolitan schools, the impact of local cultures and additional logistical barriers indicate that they may need further tailored support to aid their transition to adulthood.